Evaluation of surface roughness parameters and their impact on fatigue strength of Al-Si cast material. (2019) - Pomberger, Sebastian; Leitner, Martin; Stoschka, Michael
Abstract: Sand-cast aluminium components enable complex component designs whose surface is partly machined subsequently. Thus, the fatigue strength is affected both by volumetric shrinkage porosity as well as by surface roughness. For as-cast surface characterisation, utilization of area-based roughness parameters is essential. Fatigue tests covering T6 and HIP heat treatment as well as machined versus as-cast surface conditions are performed, whereat a change of up to fifteen percent in fatigue strength is observable. The results of this study reveal, that the mean values of the area-based surface roughness parameters Sa and St correlate well with the fatigue strength if no micro-porosity exists within the surface layer